A ROBUST WATERMARKING SCHEME AGAINTS VARIOUS ATTACKS BASED ON DCT IN FIVE DIFFERENT POSITIONS OF THE HOST IMAGE AREA - Rosiyadi, Didi; Muttaqien, Furqon Hensan (LIPI Press, 2013)
This paper proposed a robustness watermarking scheme against various attacks based on Discrete Cosine Transform (DCT) in fi ve different positions of the host image area. The scheme comprises the level of watermark resistance and the level of host image perceptibility against various attacks. Here, the level of resistance of a watermark image can be seen from the value of Normalized Correlation Coeffi cient (NC). Meanwhile, the level of perceptibility of an image of host image can be seen from the value of its Peak Signal to Noise Ratio (PSNR). In this proposed research, a method of the Non Blind Discrete in which a host image is required in the process of extraction is used. This watermark, furthermore, is positioned in a visible way in fi ve different positions of the host image; those are on the upper left, lower left, upper right, lower right and on the middle. For the type of attacks, this research uses geometric attacks consisting of Rotation, Scaling and Cropping. The result of this research then shows the level of resistance and the level of perceptibility for all images, and obtains the most robust watermark scheme against various attacks.